A universal approach for thin high-entropy oxides regulated by Ga2O3 layers for oxygen evolution reaction - Wenyang Zhang; Huixin Jin; Yanna Guo; Yinghao Cui; Jingyu Qin; Jianxin Zhang; Yusuke Yamauchi; Yoshiyuki Sugahara (Nature Communications)
Abstract High-entropy oxides (HEOs) are a class of promising materials with multielement tunability and untold scientific merits, yet the controllable preparation of nano-sized HEOs is notoriously difficult. Herein, we utilize the natural oxide layer on liquid gallium as an ideal substrate to facilitate the synthesis of thin HEO. Through experiments and density functional theory (DFT) calculations, it is found that Ga2O3 layer exhibits a strong affinity for metal ions and oxides, which not only enables it to anchor multiple metal ions and facilitate the formation of HEO, but also introduces a strain effect that can lower the free-energy barrier for oxygen evolution reaction (OER). It increases the exposed surface area and active sites of HEO, enhancing its reaction efficiency. As a result, the Ga2O3-supported thin HEO film (Mn0.65Fe0.59Co0.83Ni0.48Zn0.45O4) shows satisfactory OER performance compared with other control groups. This study exemplifies the potential of the liquid Ga2O3 layer as an affinity substrate for high-entropy material synthesis.